Investigation On Sapphire Based Mems Pressure Sensor Sensitivity Through Finite Element Method - SYED AHMAD HASBI AL IDRUS BIN SAID ABD KADIR,; Prof. Madya. Ts.Dr.Rosmila Binti Abdul Kahar,; Mirza Basyir Rodhuan,; Nur Fatimah Zahra Binti Mohd Khairi,; MOHD HAFIZUDDIN BIN ZAINOL ABIDIN,; Muhammad Danial Irfan Bin Mohd Shahar, (Enhanced Knowledge in Sciences and Technology, 2023)
In this paper, a micro-electromechanical (MEMS) capacitive pressure sensor using sapphire on the diaphragm is investigated by simulation using COMSOL Multiphysics Software. Typically, a diaphragm serves as the detecting element for this micro-pressure sensor, converting applied pressure into the appropriate displacement. Firstly, this study focused on the various shapes of diaphragms like circular, square, and rectangular. The model was developed with different thickness and materials to get the highest level of sensitivity from the shape. In order to validate the simulation method, a comparison with the results from the previous researcher has been made first. The purpose of this study is to design, simulate, and analyses the sensitivity of a MEMS capacitive pressures sensor-based diaphragm using different shapes, thicknesses and materials. The recommended pressure range is 0MPa to 100MPa. The circular shape with thin diaphragm has highest sensitivity although sapphire has low sensitivity because of its properties but it is good option for high pressure